2012
DOI: 10.1016/j.eatbeh.2011.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Associations between eating patterns, dietary intakes and eating behaviors in premenopausal overweight women

Abstract: The regulation of energy intake is complex and many biological, psychosocial and environmental influences have been identified. To our knowledge, no study has yet investigated how eating patterns could mediate associations between eating behaviors and self-reported energy intake in premenopausal overweight women. Therefore, objectives of this study were to examine associations between eating behaviors and eating patterns in premenopausal overweight women and to test if Eat Behav. 2012 Apr;13(2):162-5. doi: 10.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 26 publications
4
12
0
Order By: Relevance
“…However, the finding that the strength of this association changes throughout a typical day with peaks in evening hours is relatively novel. In support of our observation, a recent study by Leblanc et al (2012) demonstrated that emotional eating, which is closely related to stress eating, was positively associated with a higher proportion of energy intake from snacks after 5:00 pm. It was suggested that “this loss of control (overeating) later in the day” (p. 164) was likely related to declines in satiety over the course of the day (de Castro, 2001, 2004, 2009; de Castro, Bellisle, Feunekes, Dalix, & DeGraaf, 1997), but, from the current study, it can be suggested that stress-induced hunger could additionally contribute to excessive energy intake in the evening.…”
Section: Discussionsupporting
confidence: 91%
“…However, the finding that the strength of this association changes throughout a typical day with peaks in evening hours is relatively novel. In support of our observation, a recent study by Leblanc et al (2012) demonstrated that emotional eating, which is closely related to stress eating, was positively associated with a higher proportion of energy intake from snacks after 5:00 pm. It was suggested that “this loss of control (overeating) later in the day” (p. 164) was likely related to declines in satiety over the course of the day (de Castro, 2001, 2004, 2009; de Castro, Bellisle, Feunekes, Dalix, & DeGraaf, 1997), but, from the current study, it can be suggested that stress-induced hunger could additionally contribute to excessive energy intake in the evening.…”
Section: Discussionsupporting
confidence: 91%
“…Regular meal patterns have been shown to lead to higher postprandial energy expenditure, lower energy intake, and improved insulin sensitivity compared to irregular eating patterns in experimental studies of lean and obese women [11,12]. A recent study in premenopausal women concluded that meal pattern is an important factor that can explain the associations between eating behaviors and self-reported energy intake [13]. However, no previous study have investigated whether meal patterns of women with PCOS differ from those of healthy women.…”
Section: Introductionmentioning
confidence: 97%
“…Numerous studies have examined dietary restraint to investigate the extent to which differences in restraint were systematically related to caloric intake, body mass index (BMI) and weight change (Finlayson, Cecil, Higgs, Hill, & Hetherington, 2012;Laessle et al, 1989;Leblanc et al, 2012;McLean & Barr, 2003;Westenhoefer et al, 1994). Available data have shown that women who scored high on dietary restraint did, in fact, restrict food intake (McLean & Barr, 2003), but with varying degrees of success.…”
Section: Introductionmentioning
confidence: 98%